The Comparison of Hydration Effect of 1% Aloe Vera Extract Cream and 10% Urea Cream as Moisturizer for Non Dermatotic Skin - Fajar Waskito, Laily Noor Qomariah, Sunardi Radiono, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Xerotic or dry skin is a condition with manifestation of scaly, coarse skin with itchy sensation. Moisturizers have been used as treatment to alleviate xerotic skin. Aloe vera is a traditional medicinal plant which has been used as skin moisturizer for a long time, however, the hydration effect of this material had not been studied. Urea is a humectant material that has been widely used as moisturizer. Objective: This study was aimed to compare the hydration effects of 1 % Aloe vera extract cream with 10% urea cream as moisturizer for non-dermatotic dry skin. Methods: This research was a single-blinded randomized controlled trial. Thirty research subjects who met inclusion criteria were given 2 types of interventions (1 % Aloe vera extract cream or 10% urea cream). Randomization was conducted to determine which cream was applied on the subjects lower arm. Cream was given as a single application. Evaluation of stratum corneum hydration level was conducted objectively using corneometer instrument: before application, 30 minutes, 1 hour, 2 hours, 3 hours and 4 hours after single application. Data of the two groups were analyzed with paired t-test. Results: There was no significant difference of stratum corneum hydration level between 1 % Aloe vera extract cream treatment and 10% urea cream at each time of measurement (p > 0.05). Conclusion: 1 % Aloe vera extract cream showed similar or equivalent hydration effect with 10% urea cream as moisturizer for non-dermatotic dry skin. Key words: aloe vera - urea - skin moisturizer - skin hydration.